The Implications of Intellectual Property Utilization on Product Innovation in MSMEs - Allingson Simanjuntak (Green Publisher Indonesia, 2026)
The growth of product innovation in the Micro, Small, and Medium Enterprises (MSME) sector is greatly influenced by the utilization of intellectual property rights (IPR) as an instrument of protection and competitive advantage. IPR provides legal protection for creative and innovative outputs, allowing MSME actors to enhance added value, expand markets, and reduce the risk of intellectual property infringement. However, the utilization of IPR by MSMEs in Indonesia still faces various obstacles, including limited outreach, high registration costs, and weak legal enforcement. This article analyzes the implications of IPR utilization on MSME product innovation in Indonesia based on case studies, national literature, and comparisons with international practices. The research method used is a qualitative approach, utilizing interviews, observations, documentation, and literature studies to gather data. Research findings show that increasing IPR literacy and improving access to legal protection can encourage product innovation while enhancing competitiveness and the contribution of MSMEs to the national economy. In conclusion, this study highlights the crucial role of IPR in fostering innovation and competitiveness in the MSME sector, while also emphasizing the need for improved education, simplified registration processes, and stronger government support to overcome existing barriers.